Um estudo de estresse através dos níveis de cortisol em crianças - Mendes, Karine Zanuto (Universidade Federal de São Carlos, 2017)
The level of cortisol is considered as a measure of people’s stress. We perform an statistical analysis of the data from a study conducted to evaluate if children that work on the streets during the day have higher stress than children who does not work. The cortisol level of a person can be considered as an increasing function until reaching a maximum level and then decreasing to almost zero (quasi-concave function). Children’s cortisol were collected 4 times in one day, where two groups of children were considered: those who work in the street and those who stay at home. To analyse the data we considered a meta-analysis of a functional data model under Bayesian approach. Each individual is analysed by a functional data model,and then, a meta-analysis was used to have inference for each group. We used the Gibbs Metropolis-Hastings method to sample from the posteriori distribution. Also,we calculated the pointwise posterior probability of the cortisol function of one group being greater than the cortisol function of other group to compare the groups.
A study of stress through cortisol levels in children
Keywords: Eixo HPA; Cortisol; Dados funcionais; Estatística bayesiana; Metanálise; HPA axis; Functional data; Bayesian statistics; Meta-analysis; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA